Instrumental and Emotional Support in Breastfeeding Fathers and Exclusive Breastfeeding Success - Carin, Vivien; Stefani, Megah; Fadlina, Athiya (Indonesian Journal of Human Nutrition, 2024)
Fathers’ support is a key factor in the success of exclusive breastfeeding. This study analyzed the relationship between fathers’ emotional and instrumental support and the success of exclusive breastfeeding. This cross-sectional study involved 33 fathers from the “Ayah ASI” community and was conducted from March to July 2024. Data were collected online using the Partner Breastfeeding Intention Scale (PBIS) questionnaire and analyzed using the Spearman correlation test. Results showed that 90.9% of the children were exclusively breastfed. Among these, 93.8% of fathers who provided good instrumental support had children who were exclusively breastfed, compared to 92.3% with sufficient support and 75.0% with poor support. For emotional support, all fathers in the “good” category had exclusively breastfed children, compared to 87.5% in the “sufficient” and 50.0% in the “poor” category. Emotional support was significantly correlated with exclusive breastfeeding success (r = 0.354, p = 0.043), while instrumental support showed a weak, non-significant correlation (r = 0.146, p = 0.416). Thus, emotional support from fathers has a stronger association with exclusive breastfeeding success than instrumental support. Interventions should prioritize enhancing fathers’ emotional engagement while continuing to support their practical involvement in breastfeeding.